International and Comparative Studies in Information and Library Science: A Focus on the United States and Asian Countries - Liu, Yan Quan; Cheng, Xiaojun (Libraries and librarianship--an international perspective ; no. 3, 2008)
Keywords: Asia; Asia; Information science; Comparative librarianship; International librarianship; Library science; United States; Information science; United States; Library science; dept.ils; faculty_collection

Evaluation of federated searching options for the school library - Abercrombie, S.E. (School Library Media Research, 2008)
Three hosted federated search tools, Follett One Search, Gale PowerSearch Plus, and WebFeat Express, were configured and implemented in a school library. Databases from five vendors and the OPAC were systematically searched. Federated search results were compared with each other and to the results of the same searches in the database's native interface to disclose differences in handling query syntax, searching, retrieval, browsing results, etc. Each product was easily configured, but none were capable of searching every database desired. Simpler Boolean queries are the most successful queries because of the underlying structure and differences of the databases, and the capabilities of certain products. Federated search products succeed in simplifying access to multiple database resources at school, but searching remains different from the familiar Web search engines in many ways. To become more Google-like, federated searching must be done against indexes built in advance instead of the current real-time searching method.
Keywords: dept.ils; ⛔ No DOI found

Citation searching: Search smarter & find more - Hammond, C.C.; Brown, S.W. (Computers in Libraries, 2008)
All in all, citation searching is a wonderful way to build a comprehensive body of knowledge. The databases allow you to follow a trail of cited references that weaves a web of information across the boundaries of time and subject limitations. It eliminates your need to know appropriate synonyms or subject-specific lingo in order to perform effective searches that yield inclusive results. Citation searching saves time while also increasing the likelihood that your search results will be appropriate for your needs. Citation searching is not just useful for librarians but for other searchers as well. If you need a comprehensive literature review - whether you're a librarian, faculty member, student, or scientist - you would benefit greatly from the capabilities of citation searching databases. The training program for citation searching at the University of Connecticut taught graduate students all these tricks and more. Students who attended our sessions now know how to do broad, interdisciplinary searches after they have searched their primary subject database. They also understand how to "chain" from the original article to the "backward" citations in that article and to the "forward" articles that cited the original. Finally, they see how they can use citation databases to find information about who's citing their articles, which they can use for job searching and grant proposals, promotion, and tenure. Try it yourself - you're sure to find something new!
Keywords: dept.ils; ⛔ No DOI found